Neuronal Correlates of Cross-Modal Transfer in the Cerebellum and Pontine Nuclei - Campolattaro, Matthew M. (Society for Neuroscience, 2011)
Cross-modal transfer occurs when learning established with a stimulus from one sensory modality facilitates subsequent learning with a new stimulus from a different sensory modality. The current study examined neuronal correlates of cross-modal transfer of pavlovian eyeblink conditioning in rats. Neuronal activity was recorded from tetrodes within the anterior interpositus nucleus (IPN) of the cerebellum and basilar pontine nucleus (PN) during different phases of training. After stimulus preexposure and unpaired training sessions with a tone conditioned stimulus (CS), light CS, and periorbital stimulation unconditioned stimulus (US), rats received associative training with one of the CSs and the US (CS1–US). Training then continued on the same day with the other CS to assess cross-modal transfer (CS2–US). The final training session included associative training with both CSs on separate trials to establish stronger cross-modal transfer (CS1/CS2). Neurons in the IPN and PN showed primarily unimodal responses during pretraining sessions. Learning-related facilitation of activity correlated with the conditioned response (CR) developed in the IPN and PN during CS1–US training. Subsequent CS2–US training resulted in acquisition of CRs and learning-related neuronal activity in the IPN but substantially less little learning-related activity in the PN. Additional CS1/CS2 training increased CRs and learning-related activity in the IPN and PN during CS2–US trials. The findings suggest that cross-modal neuronal plasticity in the PN is driven by excitatory feedback from the IPN to the PN. Interacting plasticity mechanisms in the IPN and PN may underlie behavioral cross-modal transfer in eyeblink conditioning.